TRIBAL USES OF MEDICINAL PLANTS OF RAJASHTHAN:KACHNAR: Life Science-Ethno botany - SHARMA, SANTOSH; KUMAR, ASHWANI (International Journal of Life Science and Pharma Research, 2012)
Ethnobotany can be defined as the total natural and traditional relationship and the interactions between man and his surrounding plant wealth from times immemorial, due to sheer, necessity, intution, observation and experimentation. Ethnobotany of India might is among the earliest in the world and all traditional systems of medicine had their roots in ethnobotany. Rajasthan has rich cultural diversity and biodiversity. Around seven percent of tribals of India live in Rajasthan. Present paper presents use of medicinal plants by tribal people in general and Rajasthan in particular. Bauhinia sp Kachnar are important ingredients of tribal and traditional systems of medicine